Frozen–Thawed Embryo Transfer Cycles Have a Lower Incidence of Ectopic Pregnancy Compared With Fresh Embryo Transfer Cycles. (September 2018) - Zhang, Xinyu; Ma, Caihong; Wu, Zhangxin; Tao, Liyuan; Li, Rong; Liu, Ping; Qiao, Jie
Objective: To evaluate the risk of ectopic pregnancy of embryo transfer. Design: A retrospective cohort study on the incidence of ectopic pregnancy in fresh and frozen–thawed embryo transfer cycles from January 1 st, 2010, to January 1 st, 2015. Patients: Infertile women undergoing frozen–thawed transfer cycles or fresh transfer cycles. Intervention: In-vitro fertilization, fresh embryo transfer, frozen–thawed embryo transfer, ectopic pregnancy. Main Outcome Measures: Ectopic pregnancy rate and clinical pregnancy rate. Result: A total of 69 756 in vitro fertilization–embryo transfer cycles from 2010 to 2015 were analyzed, including 45 960 (65.9%) fresh and 23 796 (34.1%) frozen–thawed embryo transfer cycles. The clinical pregnancy rate per embryo transfer was slightly lower in fresh embryo transfer cycles compared with frozen–thawed embryo transfer cycles (40.8% vs 43.1%, P < .001). Frozen–thawed embryo transfer is associated with a lower incidence of ectopic pregnancy per clinical pregnancy, compared with fresh embryo transfers (odds ratio = 0.31; 95% confidence interval = 0.24-0.39). Female age and body mass index have no influence on ectopic pregnancy. In the frozen–thawed embryo transfer cycles, blastocyst transfer shows a significantly lower incidence of ectopic pregnancy (0.8% vs 1.8%, P = .002) in comparison with day 3 cleavage embryo transfer. Conclusion: The risk of ectopic pregnancy is lower in frozen–thawed embryo transfer cycles than fresh embryo transfer cycles, and blastocyst transfer could further decrease the ectopic pregnancy rate in frozen–thawed embryo transfer cycles.